BENIGN NEGLECT OF COVENANT VIOLATIONS: BLISSFUL BANKING OR IGNORANT MONITORING? - Stefano Colonnello; Michael Koetter; Moritz Stieglitz (Economic Inquiry, 2020)
Theoretically, bank's loan monitoring activity hinges critically on its capitalization. To proxy for monitoring intensity, we use changes in borrowers' investment following loan covenant violations, when creditors can intervene in the governance of the firm. Exploiting granular bank-firm relationships observed in the syndicated loan market, we document substantial heterogeneity in monitoring across banks and through time. Better capitalized banks are more lenient monitors that intervene less with covenant violators. Importantly, this hands-off approach is associated with improved borrowers' performance. Beyond enhancing financial resilience, regulation that requires banks to hold more capital may thus also mitigate the tightening of credit terms when firms experience shocks. (JEL G21, G32, G33, G34)
Keywords: 330